Initial survey on microplastic waste in coastal water in Nam Dinh - Nam, Phuong Ngoc; Pham , Quoc Tuan; Ngo Thi, Xuan Thinh; Nguyen Thi, Minh Diep; Duong, Thi Thuy; Le Thi, Phuong Quynh; Le, Nhu Da; Phuong, Ngoc Anh; Duong, Thanh Nghi; Le, Quy Thuong (Vietnam Journal of Marine Science and Technology, 2022)
Plastic materials are defined as including the whole of organic polymers owning plasticity. Their production increases rapidly due to their superior properties and applications in our life. Currently, the annual production of plastic is estimated at nearly 400 million tons. About 10% of the plastic produced is discharged into the seas and oceans. Microplastics (MP, less than 5 mm in size) are non-biodegradable and persistent in the environment and have the ability to accumulate in various environmental components, organisms and other human beings through the food chain. Therefore, assessing microplastic pollution becomes essential for the marine and ocean environment. This study aims to evaluate microplastic pollution in Nam Dinh seawater. Water samples were taken in summer 2020 and spring 2021 in Giao Thuy district, Nam Dinh province. Samples were treated with 30% H2O2 solution to remove organic matters and then microplastic buoyantly separated using saturated NaCl solution. MP was identified through observation under a stereo microscope (Olympus SZX2-TR300) and its nature was determined through infrared spectroscopy (µFTIR). Results show that a large level of pollution (average 6 to 8 particles/m3 and 10–14 million particles/km2) is associated with the predominant of colored fibers among MP characteristics. Most of the microplastics identified are Polypropylene in nature. Next, more research needs to be invested in this pollution problem, such as expanding the scope and research object.